Framework Authentication e-document using Blockchain Technology on the Government system - Isyak Meirobie; Agustinus Purna Irawan; Husni Teja Sukmana; Diana Putri Lazirkha; Nuke Puji Lestari Santoso (International Journal of Artificial Intelligence Research, 2022)
As a sophisticated platform, namely Blockchain, which has 3 (three) potentials to change the governance system which is still considered traditional, solve the problem of principal agents, and minimize the crime of document falsification. However, in the government sector, the documents used can be insecure and lead to document falsification. Blockchain is becoming increasingly significant in document services and beyond until questions arise about the authenticity and security of manuscripts and documents in the government sector. So, Go-Chain (Government Blockchain) it is necessary to authenticate documents using Blockchain to minimize document forgery. By utilizing the potential of Blockchain technology, this research aims to maximize government e-documents in a modern and secure manner. Propose a Blockchain-based document framework method that is applied with a literature review study—in addition to ensuring the speed of system execution by utilizing DAO (Decentralized Autonomous Organization) and Smart Contracts. The result is that modern and safe government e-documents in document verification can significantly maintain transparency and increase trust in public services.